2017
DOI: 10.1063/1.4981868
|View full text |Cite
|
Sign up to set email alerts
|

Review on thermal insulation performance in various type of concrete

Abstract: Abstract. Thermal insulation concrete building plays an important role in environment sustainability especially energy saving buildings. Buildings are one of the largest consumers of energy worldwide. Therefore, significant energy saving can be realized by buildings with proper materials, design and operation. Thermal insulation systems are nowadays mostly applied for such building envelopes where the materials of load bearing structure such as concrete do not have a substantial thermal insulation capability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The material used for the purpose of the study was received from Omega Minerals, Germany. The concrete mix formulas used the aggregate with the grain diameter 0.5 mm and bulk density 0.8 g/cm 3 .…”
Section: Omega-spheresmentioning
confidence: 99%
See 1 more Smart Citation
“…The material used for the purpose of the study was received from Omega Minerals, Germany. The concrete mix formulas used the aggregate with the grain diameter 0.5 mm and bulk density 0.8 g/cm 3 .…”
Section: Omega-spheresmentioning
confidence: 99%
“…Waste aggregate can be used as an alternative material to produce lightweight concrete with low environmental impact [1,2]. In order to meet the existing numerous requirements, the manufacturers of building materials have been constantly modifying the composition of concrete mix for obtaining the best possible parameters [3]. The question remains open whether such improvements might be converted into real benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has also been a significant increase in the use of lightweight concrete blocks to improve thermal insulation [ 53 ]. It has been observed that lightweight concrete (LWC) is a good material for the thermal insulation of structures [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Buildings are regarded as shelters and designed for thermal comfort, especially in regions with harsher climates [ 4 , 5 ], and the thermal fluctuations that are frequent occurrences in these regions resulted in increased energy consumption per building via its respective internal thermal regulation systems (air-conditioners and heaters) [ 6 , 7 ]. Passive insulation systems are seen as a less energy-intensive option for buildings in harsher climates, which has the net benefit of decreasing energy costs and being eco-friendly [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The specific heat is defined as the amount of heat per unit mass required to change a material’s temperature by one degree (1°). Specific heat is influenced by moisture content, temperature, concrete density, and aggregate type [ 9 , 44 ]. The value of the specific heat of standard concrete varies between 0.8–1.8 MJ/m 3 K [ 45 ].…”
Section: Introductionmentioning
confidence: 99%